Solitary HERV-K LTRs possess bi-directional promoter activity and contain a negative regulatory element in the U5 region - Domansky, Andrey N.; Kopantzev, Eugene P.; Snezhkov, Eugene V.; Lebedev, Yuri B.; Leib-Mösch, Christine; Sverdlov, Eugene D. (FEBS letters, 2000)
Reporter gene analysis of HERV-K solitary long terminal repeats (LTRs) showed that they retain detectable activity in human teratocarcinoma cells, and can direct the transcription in both orientations relative to the reporter gene. Deletion analysis demonstrated the possible existence of alternative promoters within the LTR as well as a silencer-like element in the U5 region. Our results indicate also that all-trans-retinoic acid is capable of modulating expression of the reporter gene directed by a HERV-K LTR in NT2/D1 cells.
Gesehen am 27.05.2022